Imagination, form, movement and sound: Studies in musical improvisation - Tandberg, Svein Erik (Gothenborg University of Gothenborg, 2008)
How does one improvise? How can one learn the art of improvisation? By considering these two questions this thesis aspires to make a contribution towards a greater understanding of what the production of improvised music actually involves. The organ has long traditions as an instrument on which music is improvised, and this study aims to focus primarily on organ improvisation. It is assumed that spontaneous impulses, rational thought and an extensive array of physical movements have their origins in the emotional, intellectual and physical aspects of a person. These different facets of a person, which continually interact with and influence each other, form a complex series of behaviour patterns. It can be useful to experience the interactive energy between these facets in order to approach an understanding of improvisation. This hypothesis is based on an assumption that improvised music is created by an interaction between large numbers of internalised concepts of musical sound, along with a corresponding array of precise physical movements. The sounds are expressed through the actions of the improviser. Ideally these actions will have their origins in more or less welldefined aesthetic concepts. Thus the hypothesis of this research is that it is in the light of the improvisers different perceptions of the words imagination and form that the musical train of events is set in motion. This study should be regarded as artistic research. The term artistic defines a research position that is related to an actual artistic practice. The work incorporates elements which can be described as creative research. This means that researches do not only form a subject for discussion, but have actually resulted in the creation of three different recording projects presented on four CDs. These musical manifestations are intended to serve both as demonstrations of working methods whilst also functioning as reference points. Since art both consists of deeds and thoughts the aim here is to probe the links between practical and theoretical aspects of improvisation. The recordings should thus be regarded as a medium to emphasise and give added weight to the arguments. The study is divided into two main sections. The first part focuses on the art of organ improvisation as practised during different periods of history, whilst the second part considers the aesthetical and practical aspects involved. The question as to how differing forms of an improvisatory vocabulary can be acquired, assimilated and developed will occupy a prominent position in this latter section.
Academic dissertation which, with the permission of the Faculty of Arts at the University of Gothenburg for the award of a doctoral degree, is submitted for public review 28 august 2008